Strength Assessment of Prosthetic Pylon Considering the Geometric of Raw Material - Syaifudin, Achmad; Suryandari, Dika Andini; Agustin, Helena Carolina Kis (Journal of Medicine and Health Technology, 2024)
Prosthetic limbs are crucial as assistive devices for individuals with lower limb amputations. This study focuses on designing and analysing prosthetic feet, specifically the telescopic tube component, to achieve optimal material strength and aesthetic appeal. Numerical simulations using ANSYS Workbench 19 are conducted to assess the total deformation and von Mises stress. Design iterations adjust the pylon tube thickness and material selection. Prototypes are developed using aluminium 6061 tube and rod materials for further testing. Various tests, including scanning electron microscopy, metallography, axial tensile testing, and tangential tensile testing (according to ASTM B 557M), are performed to evaluate the material properties. Results indicated that the axial and yield strengths of the aluminium 6061 rod are superior to the tube type. Conversely, the aluminium 6061 tube exhibits higher ultimate and yield stability in tangential testing. Ultimately, the study concludes that the aluminium 6061 tube material is more robust and suitable for prosthetic feet.